'Our Friends in the North': Responses to the Independence Debate in the North East and Cumbria. Issue 3 (August 2014) - Shaw, Keith
<x xml:space="preserve">Abstract</x> The increasingly contested nature of the debate on Scottish independence has served to reinforce deeply-rooted fears in the North East and Cumbria over the economic implications of a more powerful Scotland. If anything, recent fraternal overtures from the Scottish Government have tended to lead to a hardening of the attitudes of those initially opposed to independence. However, this article also captures other responses which are underpinned by a clear sense of the common bond that exists between the North East, Cumbria and Scotland. Different conclusions have been drawn from this sense of being close 'neighbours', 'cousins' or 'friends'. For some, independence will fracture this close relationship, while for others the possibility of an independent Scotland should be used to gain leverage when arguing for devolving greater power within England itself. There are also signs that a more hopeful view is emerging just south of the border: one that has used the deliberative opportunities created by the referendum campaign to highlight how greater cross-border collaboration could be taken forward irrespective of the outcome of the September 18th vote.